Highly active repeat-mediated recombination in the mitogenome of the holoparasitic plant Aeginetia indica - Zhong, Yan; Yu, Runxian; Chen, Jingfang; Liu, Ying; Zhou, Renchao (Frontiers in Plant Science, 2022)
Mitogenomes of most flowering plants evolve slowly in sequence, but rapidly in structure. The rearrangements in structure are mainly caused by repeat-mediated recombination. However, patterns of repeat-mediated recombination vary substantially among plants, and to provide a comprehensive picture, characterization of repeat-mediated recombination should extend to more plant species, including parasitic plants with a distict heterotrophic lifestyle. Here we assembled the mitogenome of the holoparasitic plant Aeginetia indica (Orobanchaceae) using Illumina sequencing reads. The mitogenome was assembled into a circular chromosome of 420,362 bp, 18,734 bp longer than that of another individual of A. indica which was assembled before as a linear molecule. Synteny analysis between the two mitogenomes revealed numerous rearrangements, unique regions of each individual and 0.2% sequence divergence in their syntenic regions. The A. indica mitogenome contains a gene content typical of flowering plants (33 protein-coding, 3 rRNA, and 17 tRNA genes). Repetitive sequences >30 bp in size totals 57,060 bp, representing 13.6% of the mitogenome. We examined recombination mediated by repeats >100 bp in size and found highly active recombination for all the repeats, including a very large repeat of ~16 kb. Recombination between these repeats can form much smaller subgenomic circular chromosomes, which may lead to rapid replication of mitochondrial DNA and thus be advantageous for A. indica with a parasitic lifestyle. In addition, unlike some other parasitic plants, A. indica shows no evidence for horizontal gene transfer of protein-coding genes in its mitogenome.